Evaluating upper versus lower calyceal access in percutaneous nephrolithotomy: a prospective comparative study in complex renal calculi - Mishra, Navneet; Singh, Ashish Kumar; Chandra Vamsi Krishna, M.; Gautam, Umesh; Mishra, Manoj Kumar (International Journal of Research in Medical Sciences, 2025)
Background: Percutaneous nephrolithotomy (PCNL) is the preferred modality for managing complex renal calculi, yet the optimal calyceal access upper or lower remains debated due to varied outcomes and complication profiles. Methods: The research included 100 patients undergoing PCNL for treatment of complex renal stones. A division of patients occurred into two distinct groups: those accessing the upper calyces with n=46 and those accessing the lower calyces with n=54. Medical staff evaluated stone size together with operative time and haemoglobin drop and stone clearance and hospital stay duration. Results: Finding shows operative durations (84.35 min vs. 84.66 min, p>0.05), baseline stone sizes (39.07 mm vs. 39.41 mm, p>0.05), haemoglobin decline (1.58 vs. 1.57 gm%, p>0.05) and hospital stay (3.80 vs. 3.67 days, p>0.05) were similar for both groups. Though the variation was not statistically noteworthy (p>0.05), the upper calyceal group (86.96%) had a greater total stone clearance rate than the lower (75.93%). Conclusions: Regarding operative time, safety and recuperation, upper and lower calyceal access in PCNL produced similar clinical results. Upper calyceal access, on the other hand, indicated a tendency toward improved stone clearance, implying possible clinical preference in certain complicated situations.